The Constitutionality of the Policy of Granting Limited Stay Visas as an Instrument to Increase Investment in Indonesia - Raden Nicky Fitria Jackhariyas; Hamdan Azhar Siregar (Green Publisher Indonesia, 2026)
The problems that exist in Indonesia, which require the state to attract foreign investment, are also caused by other factors, particularly the benefits or profits received by the country. The form of research used in this thesis is normative juridical research, which refers to legal norms contained in laws and regulations. This study employs a statutory approach and a conceptual approach. The data in this study were analyzed qualitatively, meaning that the research method refers to legal norms contained in statutory regulations. The results of this study indicate that the relationship between business law and immigration law in relation to foreign investment is regulated under Law Number 11 of 2020 concerning Job Creation. Philosophically, and in the spirit of globalization, the use of foreign workers in developing countries is intended to facilitate the transfer of knowledge and technology. This is in line with the continuity of business and investment in Indonesia. The issuance of Limited-Stay Visas for foreign investment, from the perspective of business law, constitutes a form of state sovereignty within a rule-of-law state, which has full authority to determine and regulate the limits for foreigners residing in a country. Restrictions on residence permits are intended to protect national interests in social, cultural, economic, employment, security, and public order aspects.